EMERGING CHALLENGES OF TEACHING ENGLISH IN NON-NATIVE ENGLISH-SPEAKING COUNTRIES: TEACHERS’ VIEW - Hasanah, Nurul; Utami, Pratiwi Tri (Universitas Ahmad Dahlan, 2019)
Teaching English to students, particularly non-English speakers, requires proper strategies and methods. By doing so, each teacher has his/her challenges. This study intends to unveil the emerging challenges faced by English teachers from non-native English-speaking countries (non-NESCs) such as China, Japan, Thailand, Senegal, Mongolia, Cambodia, and Laos. This study stands on to answer two research questions: 1. What are the challenges of teaching English in non-native English-speaking countries? 2. Is there any effort to overcome the challenges? If so, how do they overcome it? By utilizing the qualitative method, seven teachers are interviewed to tell their challenges. The result indicates three main problems, including learning materials which do not cover students? need, too big classroom size and school environment, and also students? low motivation. Some programs are conducted to overcome those challenges. For example, Japan has an Assistant Language Teacher (ALT) who comes once a week to cooperate with the English teacher in each school. Then, Volunteer English Teacher (VET) program helps English Teachers in Laos.